The category of ‘family workers’ in International Labour Organization statistics (1930s-1980s): a contribution to the study of globalized gendered boundaries between household and market - Wobbe, Theresa; Renard, Léa (Journal of global history, 2017)
This article discusses the role that statistical classifications play in creating gendered boundaries in the world of work. The term ‘family worker’ first became a statistical category in various Western national statistics around 1900. After 1945, it was established as a category of the International Labour Organization (ILO) labour force concept, and since then it has been extended to the wider world by way of the UN System of National Accounts. By investigating the term ‘family worker’ from the perspective of internationally comparable statistical classification, this article offers an empirical insight into how and why particular concepts of work become ‘globalized’. We argue that the statistical term ‘economically active people’ was extended to unpaid family workers, whereas the distinction between family work and housework was increasingly based on scientific evidence. This reclassification of work is an indication of its growing comparability within an economic observation scheme. The ILO generated and authorized that global discourse, and, as such, attested to an increasingly global form of knowledge and communication about the status of gender and work.
Gesehen am 02.05.2023